Employers' experiences with safe work integration of recent immigrants and refugees. (November 2022) - Yanar, Basak; Nasir, Kay; Massoud, Amani; Usmani, Sibghat; Premji, Stephanie; Smith, Peter
Highlights: Employers identified challenges related to limited OHS knowledge and awareness of newcomer workers, language barriers, perceived cultural differences, and resource needs related to safety. The findings identified gaps in employer safety practices and safety communication in integrating recent immigrants and refugees safely into work. Providing resources to employers on different approaches to train newcomer workers with language challenges and positive ways to work with cultural diversity may create safer workplaces. Abstract: Despite their important role in the safe and sustained work integration of newcomers to Canada, little is known about employers' expectations, experiences and challenges in relation to safely integrating recent immigrants and refugees to work. In-depth, semi-structured interviews were conducted with 35 employer representatives, 21 service providers, and five other key informants to understand employers' experiences, challenges, and resource needs related to safe work integration of newcomer workers. An exploratory qualitative approach was used to collect and analyze the data. Employers tended to focus on individual attributes of newcomers, such as newcomer workers' lack of health and safety knowledge and awareness, and limited language capacity as important drivers of workplace health and safety among newcomers. They also discussed their own resource needs as key challenges in managing workplace health and safety. Employers often attributed lack of safety knowledge and awareness of newcomer workers as being due to cultural differences in relation to the priority given to safety and safe work practices. There were gaps identified in employer practices, such as top down approaches in training and communication and a focus on culture and individual responsibility in explaining challenges related to managing health and safety. Our findings suggest that providing resources to employers to train newcomer workers in a way that takes into account language barriers and diverse cultural practices may create safer workplaces for all workers, but particularly for those hiring new immigrants.